The prevalence and clinicopathological profile of IgM nephropathy in children with steroid-resistant nephrotic syndrome at a single centre in Pakistan. Issue 12 (28th August 2012) - Shakeel, Shaheera; Mubarak, Muhammed; Kazi, Javed I; Lanewala, Ali
Abstract : Background: There is little information on the clinicopathological characteristics of IgM nephropathy (IgMN) in paediatric steroid-resistant nephrotic syndrome (SRNS) and its response to calcineurin inhibitors (CNI). Material and Methods: This study was conducted at Sindh Institute of Urology and Transplantation, from January 2009 to August 2011. All SRNS children who received renal biopsies were included. Relevant data were compared among minimal change disease (MCD) and IgMN. The response to CNI was analysed in detail in IgMN by groups (group 1: complete or partial remission; group 2: no response). Results: The frequency of IgMN in 147 children with SRNS was 13.6%. Compared with MCD, there was a male preponderance in IgMN. Blood urea and serum creatinine both at presentation and at last follow-up were significantly higher in IgMN. Regarding subgroups of IgMN, systolic blood pressure (SBP), blood urea and serum creatinine were significantly higher in group 2 at presentation, while at last follow-up, SBP, diastolic blood pressure and proteinuria were higher in group 2. The prevalence and degree of mesangial proliferation, global glomerulosclerosis, interstitial fibrosis and tubular atrophy were significantly higher in group 2. Conclusions: IgMN is a common cause of paediatric SRNS and is significantly different from MCD. There is also a significant difference in clinical and laboratory parameters among responders and non-responders to CNI in IgMN.